Record dengue deaths in Bangladesh as disease patterns change - Roney, Miah; Huq, A. K. M. Moyeenul; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier B.V., 2024)
The worst dengue outbreak to ever strike Bangladesh was in 2023, caused by the DENV-2 strain. The Directorate General of Health Service (DGHS) estimated case fatality rate of 0.53 % in 2023 based on a total of 32,1179 laboratory-confirmed cases and 17,05 associated fatalities. The outbreak has spread to all eight divisions of the nation and displayed unique seasonality as well as an early, dramatic rise in case count, peaking in late June. Along with regional diversity in the epidemic loads, the outbreak has also shown differences in morbidity and death associated with age and gender. The government has stepped up its anti-dengue campaign in response to the crisis, including initiatives to increase public awareness and manage the mosquito population.